Darkly dreaming Dexter : a novel - Lindsay, Jeffry P. (Lindsay, Jeffry P. Dexter series, 2006)
Hiding a secret life as an assassin while working as a murder analyst for the Miami police, Dexter Morgan is intrigued by the work of a new serial killer whose style mimics his own.